THE NEW PUBLIC FINANCE IMPLEMENTATION IN THE PRODUCTION SHARING CONTRACT SCHEME FOR EXPLORATION AND EXPLOITATION OF OIL AND GAS RESOURCE IN INDONESIA - Setyadi, Didik Sasono; Mulyati, Deti; Amedi, Azeem Marhendra (NATIONAL JOURNAL of LAW, 2020)
Abstract Indonesia is a country which have oil and gas reserve as one of the country natural resources. Until now, the government management on oil and gas resources remain plays such important role in both strategic aspect as the state income contributor and the energy resilience. The Production Sharing Contract (PSC) Scheme applies in the management system of exploration and exploitation (Upstream) of oil and gas resources that is mandated by the 1945Constitution that should be managed for the greatest people prosperity. The PSC Scheme is a type of collaboration or partnership agreement between Government Institution (Representative) with Private Parties (National or Multi-National Corporation) to mutually explore and exploit the resources for the purpose of the Government mission (to provide people prosperity) in one hand, and to produce added value for the private corporation on the other hand. PSC Scheme has been enabling both parties joint and share genera and technical management aspect, asset management aspect, as well as financial / fiscal aspect encompass, therefore this scheme should be considered as part of the New Public Finance in implementation; Key Words: New Public Finance, Production Sharing Contact, Oil and Gas Resource Exploration and Exploitation.